“Partos en añosas: incidencia y complicaciones mas frecuentes en el hospital N° 02 del distrito de Yarinacocha, Pucallpa 1993 – 1994” - Águila Fernández, María C. Del (1995)
Today the growing tendency about the gestation age, is one of the problems that brings with it various risks and diseases for the binomial Muki German; It is the reason why a study of applied research with explanatory level on 2 NQ Hospital of Yarinacocha, pucallpa for the period between 01 October 1993 to 30 September 1994. Of a total of 1084 births is found that 100 were pregnant Petunia, representing a frequency of 9.23 percent of the total. The found dystocia fetal presentation were (53.34%), funiculars (36.67%), more jumping complication in labour was toxaemia (32. 61%). Instead the complication post childbirth more frequent it make up those tears (cervical, vaginal and perineal) with a 17.07%. Is it concluded by saying that having found a significant frequency of old pregnant we act properly in the management of these pregnancies and this fo...